Teologi Politik Gereja; Menemukan dan Memancarkan Tritugas Gereja dalam Pilkada dan Pilpres: Indonesia - Hasahatan Hutahaean (Melo: Jurnal Studi Agama-agama, 2021)
This research was conducted to find the attitude of the church in responding to the practical politics around the church. Because it leads the church to determine its position in siding with one party or one particular candidate. Or the church is just a spectator in the democratic party at the National, Provincial, and maybe Regency/City levels. The research uses a qualitative approach by searching literature and field facts where the church responds to the phenomenon of democracy, especially in Indonesia. The results of the study show the importance of the church in educating its members about the rights and obligations as voice owners in a democratic system. The church should take on a role as an educator on the practice of democracy that is clean, honest, and with a national perspective based on the fear of God. The Bible teaches the church to direct one of its three vocations to politics. To create a democratic system for the welfare of the people. Churches that stay away from the political realm in the sense of education, counseling and coaching to members of the congregation do not yet understand the true meaning of politics. The guidance of the members of the congregation in their position as representatives of the people at the district/city, provincial or national level as well as the executive should be provided in a pattern that is suitable for them both in terms of time, capacity, and involvement in the church.   Penelitian ini dilakukan untuk menemukan sikap gereja dalam merespons politik praktis yang ada di sekitar gereja. Karena menuntun gereja untuk menentukan sikap dalam berpihak kepada salah satu partai atau kepada salah satu calon tertentu. Atau gereja hanya menjadi penonton dalam pesta demokrasi tingkat Nasional, Provinsi dan mungkin tingkat Kabupaten/Kota. Penelitian menggunakan pendekatan kualitatif dengan penelusuran literatur serta fakta lapangan dimana gereja merespons fenomena demokrasi khususnya di Indonesia. Hasil penelitian menunjukkan pentingnya gereja memberi edukasi warga jemaat tentang hak dan kewajiban sebagai pemilik suara dalam satu sistem demokrasi. Gereja hendaknya mengambil peran sebagai penyuluh terhadap praktik demokrasi yang bersih, jujur dan berwawasan kebangsaan yang didasarkan takut kepada Tuhan. Alkitab mengajarkan gereja mengarahkan salah satu tri tugas panggilannya kepada bidang politik. Supaya tercipta sistem demokrasi yang mensejahterahkan orang banyak. Gereja yang menjauhi ranah politik dalam arti edukasi, penyuluhan dan pembinaan kepada warga jemaat belum memahami arti politik sesungguhnya. Pembinaan terhadap warga jemaat dalam posisinya sebagai wakil rakyat di tingkat kabupaten/kota, provinsi atau nasional serta eksekutif hendaknya diberikan dengan pola yang sesuai bagi mereka baik dari sisi waktu, kapasitas dan keterlibatannya di gereja.